Epizootic and epidemic dermatophytose outbreaks caused by Trichophyton mentagrophytes from rabbits in Portugal, 2015. Issue 10 (13th June 2016) - Mesquita, João R.; Vasconcelos‐Nóbrega, Carmen; Oliveira, Jorge; Coelho, Catarina; Vala, Helena; Fratti, Marina; Arabatzis, Michael; Velegraki, Aristea; Michel, Monod
Summary: We report an outbreak of dermatophytoses in rabbits, which was the origin of a dermatophytose epidemic in an agricultural school in central Portugal, affecting 15 people. Both the phenotypic characteristics and internal transcribed spacer (ITS) sequence of the dermatophytes isolated from the rabbits and patients were identical, suggesting that a single strain was responsible for both the epizootic and epidemic dermatophytoses and confirming that these two outbreaks were linked. The ITS sequences were also 100% identical to the ITS sequence of five strains isolated from rabbits in Greece and Italy, but different from that of Trichophyton mentagrophytes commonly isolated from dogs and cats. These results suggest that a particular T. mentagrophytes genotype could be prevalent in rabbits in southern Europe.